Teacher Readiness in Implementing The Merdeka Curriculum on Viewing Skills at The Elementary School Level - Kusuma, Rizki Rahma; Rahmawati, Fitri Puji (Universitas Muhammadiyah Surakarta, 2023)
Purpose: This study aims to assess the readiness of fifth-grade teachers and delineate the incorporation of viewing skills within the Indonesian language curriculum. Methodology: The research adopts a descriptive qualitative approach employing a case study design. The participants include fifth-grade teachers, principals, and additional data sources from teacher guideline materials. Data collection methods encompass observational checks, interviews, and document analysis. Results: The findings reveal that teachers exhibit limited preparedness in embracing the Merdeka curriculum within the instructional process, consequently impacting the integration of viewing skills. Within classroom settings, the instructional approach towards viewing skills lacks interactivity and is characterised by a lack of technological or non-technological learning aids. Examination of interview transcripts, documentation, and observations of fifth-grade teachers implementing the Merdeka curriculum suggests a reliance solely on the ESPS book publisher endorsed by the school.